A comparative study on the dimensional stability of alginate impressions stored in different media - Dycoco, Yolanda B.; Jose, Joji Marie T.
Sixty alginate impressions were taken from brass molds wherein 12 impressions were poured immediately with die stone and served s the control group. The remaining 48 experimental impressions were distributed equally and stored in 4 different storage media: 2% potasium sulfate fixing solution, 2% sodium sulfate fixing solution, 2% ferrous sulfare fixing solution and make-shift humidor at 4 different time periods. Die stone was poured after a given time period and each stone cast was measured in terms of length, width, and height. Linear measurements of the experimental group were compared to those of the control group. Results obtained showed that 2% potassium sulfate and 2% sodium sulfate fixing solutions and the make-shift humidor are the best storage media for alginate impressions.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental impressions; Alginates; Dental casting